Perspectives and challenges of marine carbon dioxide removal - Oschlies, Andreas; Bach, Lennart T.; Fennel, Katja; Gattuso, Jean-Pierre; Mengis, Nadine (Frontiers in Climate, 2025)
The Paris Agreement to limit global warming to well below 2°C requires drastic reductions in greenhouse gas emissions and the balancing of any remaining emissions by carbon dioxide removal (CDR). Due to uncertainties about the potential and durability of many land-based approaches to deliver sufficient CDR, marine CDR options are receiving more and more interest. We present the current state of knowledge regarding the potentials, risks, side effects as well as challenges associated with technical feasibility, governance, monitoring, reporting and accounting of marine CDR, covering a range of biotic and geochemical approaches. We specifically discuss to what extent a comparison with direct injection of CO2 into seawater, which had been proposed decades ago and is now prohibited by international agreements, may provide guidance for evaluating some of the biotic marine CDR approaches.